Comparative Study the Efficacy of Thai Massage and Analgesic Drug (Diclofenac) to Relief Shoulder Pain - Sitikaipong, Kantamara; Tangsukruthai, Parunkul; Noothim, Preecha; Siriwong, Walairat; Onmuk, Pawinee; Limtiyayothin, Apichat (Journal of Health Science of Thailand, 2017)
The objective of this study was to compare the effectiveness of Thai massage and a analgesic drug, diclofenac, in the reduction of shoulder pain. It was conducted as a case-control study comprising of a study group and a control group, 30 volunteers eash. The study group received Royal Thai massage two times per week for four weeks; and the results were assessed during the follow-up session at 2 days after the last session. The control group received 25 mg of diclofinac, 3 doses per day for 7 days, followed by physician instruction whether addtional dosages were needed; and a similar data collection form as the study group was used. The control volunteers were appointed for following-up on day 1, 7 and 32. Assessment of effectiveness was performed by comparing the span of angle movement and pressure pain threshold; and the data were analyzed using the t-test between the 2 groups and the pair t-test within each group. It was found that most volunteers were female employees aged 31-40. The nature of their worh required long standing, long walking or desk typing. Both groups had dull shoulder pain for the period of 6 months to 1 year. As for the effectiveness assessment, volunteers in the study group had significantly better flexibility at neck and shoulder muscle (p<0.05). However, the test for shoulder pain endurance at the left and right side revealed that those who used diclofinac could endure the pain more than those who had massage. The authors concluded that Thai massand should be an option for pain reduction and improvement of joint flexibility. This traditional wisdom could also help reducing complication from routine use of analgesic medicine.